Ammonia Gas Sensing Behavior of Hybridization between Reduced Graphene Oxide and Gold Nanoparticles. (28th August 2020) - Hoa, Huynh Tran My; Lee, Kang Jea; Pham, Hoai Phuong; Doan, Tuan Anh; Nguyen, Hoang Hung; Nguyen, Tran Quang; Tran, Quang Trung; Cuong, Tran Viet
Abstract : Stack and composite are the two ways of hybridization between gold nanoparticles (AuNPs) and reduced graphene oxide (rGO) which have been fabricated and tested the ability to detect NH3 gas at room temperature. The device based on the rGO-AuNP composite structure exhibited the highest response and the fastest response and recovery time compared to stack and bare rGO. The red shift of a resonant peak in the absorption spectra and the negative shift in the binding energy of 4f5/2 peak indicated that the remarkable NH3 gas-sensing properties of this composite are mainly attributed to a chemical bonding formed between AuNPs and rGO at the defective sites. This type of interaction facilitates the electron transfer from the defect states to the AuNP surface wherein it easily reacts with the oxygen molecules in the atmosphere to create oxygen absorbents. Consequently, NH3 not only reacts with sp 3 -hybridized atoms but also reacts primarily with oxygen absorbents on the surface of AuNPs, resulting in a better sensing behavior of composite samples.